Breast cancer nuclei segmentation and classification based on a deep learning approach - Kowal, Marek; Skobel, Marcin; Gramacki, Jarosław; Korbicz, Józef (1951- ) (Zielona Góra: Uniwersytet Zielonogórski)
One of the most popular methods in the diagnosis of breast cancer is fine-needle biopsy without aspiration. Cell nuclei are the most important elements of cancer diagnostics based on cytological images. Therefore, the first step of successful classification of cytological images is effective automatic segmentation of cell nuclei.
Keywords: breast cancer; nuclei segmentation; classification; image processing